Stimulation of Creative Entrepreneurship: Utilizing Natural Materials in Healthcare through a Nanotechnology Approach - Andini, Ary; Prayekti, Endah; Wulandari, Devyana Dyah; Romdloni , Muhammad Afwan; Syafiuddin, Achmad; Sari, Widya Novita; Zain, R.A Wafiqah Aulia; Akhmad, Nur Faradila; Suryandaru, Suryandaru; Kifli, Nurolaini (Universitas Majalengka, 2025)
As the world becomes increasingly modern, technology continues to advance at a rapid pace. The rise of Artificial Intelligence (AI) has contributed to a decline in job opportunities, leading to an increase in unemployment rates. In response, the D-VI Health Analyst Study Program at UNUSA aims to nurture young entrepreneurs in the health sector by organizing seminars and training sessions on creative entrepreneurship. These focus on the utilization of natural materials in health services through a nanotechnology approach, targeting young people, medical laboratory technicians, lecturers, and students. The event featured speakers from industry and international experts to expand the knowledge of youth and the broader community. It was conducted online as part of the International Seminar on Medical Laboratory Technology (ISoMLatech), held on March 6, 2024, via Zoom, with 216 internal participants. Evaluation results showed that over 75% of participants rated the ISoMLatech event as good or very good. It is hoped that such activities will continue in the future, as they play a crucial role in enhancing the knowledge and skills of healthcare workers in advancing nanotechnology innovation within the global healthcare industry. Keyword: Nanotechnology, Natural product, Entrepreuner, Healtcare